Specially Designed Lattice Structure for Milling Cutter Supported by FEA - Hanzl, Pavel; Zetková, Ivana; Zetek, Miroslav (Manufacturing Technology Journal, 2019)
Lattice structures are one way to reduce the weight of a component while respecting its strength requirements. These structures are based on cubic cells, therefore, they are not fully applicable to rotating parts which should be lightweight. This article particularly addresses this issue. A solution is sought for how to adapt lattice structures for a milling cutter. The final redesign of the topology allows a continuous flow of generated stress into the whole body of the cutter. Further, the solid part of the milling cutter is modified for Metal Additive Manufacturing (MAM) and the functionality of the optimised cutter is verified by Finite Element Analysis (FEA). The results of the analysis are compared with a conventional cutter with the same outer shell. The findings from the static analysis indicate that the milling cutter can be considered to be competitive.
Keywords: Milling Tool; Topological Optimization; Direct Melting Laser Sintering; Metal Additive Manufacturing